2021
DOI: 10.2147/ppa.s303869
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effects of Physicians’ Communication Skills on COVID-19 Patients

Abstract: Purpose The COVID-19 pandemic has affected physician–patient communication (PPC) in multiple ways. This study aims to report on the impact of physician–patient communication (PPC) skills on COVID-19 patients’ psychology in Jordan. Sample and Methods In this study, two questionnaires were designed. The first questionnaire targeted physicians, with 72 responses, and the second questionnaire targeted patients, with 248 responses. Both questionnaires contained common sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(42 reference statements)
0
7
1
Order By: Relevance
“…In addition, communication between HCWs and patients was also investigated during the pandemic. A study in Jordan [117] found that physician-patient communication (PPC) positively affected the patient's psychological status in COVID-19. It recommended avoiding communication errors using jargon, not being available to patients, and not showing empathy in communication.…”
Section: The Responsiveness and Communication Major Dimensionmentioning
confidence: 99%
“…In addition, communication between HCWs and patients was also investigated during the pandemic. A study in Jordan [117] found that physician-patient communication (PPC) positively affected the patient's psychological status in COVID-19. It recommended avoiding communication errors using jargon, not being available to patients, and not showing empathy in communication.…”
Section: The Responsiveness and Communication Major Dimensionmentioning
confidence: 99%
“…Al-Zyoud et al aim to explore physician communication and its “psychological impact” on Covid-19 patients by implementing a two-stage questionnaire for both physician and patient perspectives. 2 Despite this, ‘patient’s psychological status’ is poorly defined in the study aims – something which is challenging given its subjective nature. In the methodology, the authors state that the study “further uncovers the extent of a positive effect of such skills on a COVID-19 patient’s psychology”.…”
Section: Dear Editormentioning
confidence: 99%
“…In the methodology, the authors state that the study “further uncovers the extent of a positive effect of such skills on a COVID-19 patient’s psychology”. 2 However, the questionnaires are designed in such a way that the outcome that is measured is the statistical agreement between what skills the physicians say they use and how these communication skills then impact how the patient feels, instead of measuring true outcomes of patient–physician interactions. A more useful method might be to have the patient respond through a questionnaire to a specific consultation or physician, where they evaluate what communication skills were used and how this impacted their experience of healthcare services.…”
Section: Dear Editormentioning
confidence: 99%
“…In the most critical cases, the lack of healthcare personnel (or even just phone contact with a physician) has also negatively affected home care, so systems that can DOI reference number: 10.18293/DMSVIVA2021-009 minimize the need for direct human intervention in monitoring patients at home can prove very valuable. However physicians' positive communication skills have a significant psychological effect on COVID-19 patients [2], so limiting direct interaction between patient and health professional may be negative from that perspective. Moreover, for such patients, in addition to the disease, typically a quarantine at home is imposed as well.…”
Section: Introductionmentioning
confidence: 99%